A recent bottleneck of Y chromosome diversity coincides with a global change in culture - Karmin, Monika; Saag, Lauri; Vicente, Mário; Wilson Sayres, Melissa A; Järve, Mari; Talas, Ulvi Gerst; Rootsi, Siiri; Ilumäe, Anne-Mai; Mägi, Reedik; Mitt, Mario; Pagani, Luca; Puurand, Tarmo; et al. (Genome research, 2015)
It is commonly thought that human genetic diversity in non-African populations was shaped primarily by an out-of-Africa dispersal 50-100 thousand yr ago (kya). Here, we present a study of 456 geographically diverse high-coverage Y chromosome sequences, including 299 newly reported samples. Applying ancient DNA calibration, we date the Y-chromosomal most recent common ancestor (MRCA) in Africa at 254 (95% CI 192-307) kya and detect a cluster of major non-African founder haplogroups in a narrow time interval at 47-52 kya, consistent with a rapid initial colonization model of Eurasia and Oceania after the out-of-Africa bottleneck. In contrast to demographic reconstructions based on mtDNA, we infer a second strong bottleneck in Y-chromosome lineages dating to the last 10 ky. We hypothesize that this bottleneck is caused by cultural changes affecting variance of reproductive success among males.